Antimicrobial Activity of Some Medicinal Plants from East and Central Part of Nepal - Subba, Bimala; Basnet, Prakash (International Journal of Applied Sciences and Biotechnology, 2014)
To evaluate the antimicrobial activities of extract of eleven plants were examined against four common bacterials. The ethanolic extracts of various plants such as Cissus repens, Hedyotis scandens, Jatropha curcas, Morus alba, Inula cappa, Equisetum ramosissimum, Osyris wightiana, Alternantheria sessilis and Hibiscus lampas investigated individually for antimicrobial activity by disc diffusion method. These were investigated against selected species of Staphylococcus aureus, Escherichia coli, Proteus vulgaris and Klebsiella pneumoniae to find the inhibitory activities of the microbes. The ethanolic extract of C. repens showed considerably high activity against P. vulgaris, E. coli and S. aureus than other extracts. DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.9697 Int J Appl Sci Biotechnol, Vol. 2(1): 88-92